The incidence and characteristics of heading in the 2019 FIFA Women`s World Cup™ - Georgieva, J.; Arnold, E. J.; Peek, K.; Smith, A.; Lavender, A. P.; Serner, A.; Fitzgerald, M.; Ma'ayah, F.; Campbell, A. (Science and Medicine in Football, 2025)
Introduction: To quantify the incidence and characteristics of purposeful heading and other head impacts in professional women`s football at the 2019 FIFA Women`s World Cup™. Methods: This cross-sectional cohort study analysed purposeful headers (uncontested and contested) and their characteristics (e.g. playing position, match situation, field location, and distance ball travelled), and other head impact events using video analysis. Total headers and head impact events, and incidence rate (IR) per 1000 match-hours were calculated for countries, positions, and other characteristics, such as location on the pitch. Results: Purposeful headers accounted for 76% of all coded events (uncontested: 71%; contested: 29%), followed by attempted headers (21%), unintentional ball-head impacts (2%), and other head impacts (1%). Headers ranged from 0 to 22 per player, per match with a mean of 4.8 [±1.2]. Of all field positions, centrebacks had the highest heading rates and wingers the lowest. Strikers performed significantly more contested headers than any other position, and significantly less uncontested headers. Most headers occurred in the middle third (48%), from free game play (72%) and from long balls (>20 m) (68%). Conclusion: The findings of this study could assist the development of player heading risk profiles, sex-specific heading guidelines, and coaching practices.